The disaster recovery handbook : a step-by-step plan to ensure business continuity and protect vital operations, facilities, and assets - Wallace, Michael, 1960- (Finance professional collection, 2011)
No organization is safe without a disaster recovery plan in place. Expanded and up to date, this is the ultimate resource.